THE INFLUENCE OF MOTIVATION, INCENTIVES AND COMPETENCIES ON THE PERFORMANCE OF OUTSOURCED EMPLOYEES (TAD) COLLECTION WITH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE AT BANK BTN BEKASI BRANCH OFFICE - Hijliansyah Marbun; Ngaliman; I Wayan Catra Yasa; Bambang Satriawan; Indrayani; Muhammad Gita Indrawan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This research was conducted to determine how much influence Motivation, Incentives and Competence have on the Performance of Collection Outsourced Employees (TAD) with Organizational Commitment as an Intervening Variable at Bank BTN Bekasi Branch Office. The method used in this research is a descriptive quantitative method that uses a survey system. Where the data collected relates to motivation, incentives, competence, organizational commitment and employee performance at the BTN Bekasi Branch Office. The type of data is quantitative with the data source to be collected from the relevant BTN Bekasi Branch Office and based on research objects that are correlated with the title of this thesis. The population in this study were collection outsourcing (TAD) employees who worked at the BTN Bekasi Branch Office. This research uses primary and secondary data obtained from respondents, where respondents will provide verbal responses and/or written responses in response to the statements given. The data collection technique uses variable measurement using a questionnaire instrument. Each employee respondent was given three questionnaire instruments to become a source of measurement for the variables studied. The results of the research show that work motivation partially has a significant and positive influence on employee organizational commitment, incentives partially have a significant and positive influence on employee organizational commitment, partial competence has a significant and positive influence on employee organizational commitment, partial organizational commitment has a significant influence and positive on employee performance, partial work motivation has a significant and positive influence on employee performance, partial incentives have a significant and positive influence on employee performance, partial competence has a significant and positive influence on employee performance, partial work motivation has a significant influence and positive towards employee performance through organizational commitment, incentives partially have a significant and positive influence on employee performance through organizational commitment, competence partially has a significant and positive influence on employee performance through organizational commitment.